Social Cognitive-Based Human Resource Performance Evaluation to Improve the Quality of Educational Institutions - Wulan Dari; Zulfita Nur Haliza; Sitti Chadidjah; Imvitahul Mawaddah (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
The quality of educational institutions is not solely determined by curriculum and facilities, but is significantly influenced by the quality of human resources, particularly teachers and educational staff. However, performance evaluations in many educational institutions tend to be administrative and result-oriented, often failing to optimally encourage professional behaviour changes. This article aims to analyze human resource performance evaluations in education as a solution to this issue from the perspective of Albert Bandura's Social Cognitive Theory. The theory suggests that individual behaviour is influenced by the reciprocal interaction between personal factors, and environment, thus performance evaluation should function not only as an evaluation tool but also as a learning process. This research adopts a qualitative approach through a literature review of relevant books and journal articles. The findings indicate that performance evaluations based on Social Cognitive Theory can enhance self-confidence, self-regulation skills, work motivation, and foster organizational learning through observation, reflection, and positive feedback. And also, this approach encourages teachers to internalize new skills, leading to a more adaptive and productive work environment. It also promotes a shift towards continuous professional development and improves collaboration among staff. Additionally, the theory-based evaluation model offers insights into individualized growth for teachers, making it a potent strategy for enhancing educational quality. This research recommends further empirical studies on the long-term impacts of Social Cognitive-based performance evaluations on institutional growth and teacher development.